Terminalidade e cuidados paliativos em unidade de terapia intensiva - Zampieri, Kelim Paim (2019)
Objectives: To analyze the therapeutic limitations and care that were indicated and used in palliative care to patients at an Intensive Care Unit of a private hospital. Methods: A descriptive, retrospective study with a quantitative approach was performed at the adult intensive care unit of a private hospital in Caxias do Sul, RS, Brazil, by means of an analysis of all records of hospitalizations between the periods of January to December 2018. Results: The initial sample consisted of 411 hospitalizations at the unit, and all records of hospitalizations from January to December 2018. As result of doing this analysis, sixty six records were found promptuaries with records of palliative care. Conclusion: The training of 9 the professionals who work at ICUs is imperative, so it is necessary to intervene and train them, seeking for improvements in the system related to this area because this topic is also linked with care provided to patients outside the therapeutic scenario. Thus, proving, a significant understanding of the processes of death as well as prioritizing the human dignity.